Return-to-Work Assessment for Traditional Tin Miners with Tuberculosis and Pneumoconiosis: A Case Report Using PERDOKI’s 7-Step Fit-to-Work Method - Heru Alfares; Yohanes Edwin; Nuri Purwito (ILUNI MKK FKUI and PRODI MKK FKUI, 2026)
Background: Workers involved in Indonesia’s traditional tin mining face significant risks of developing pneumoconiosis, primarily due to persistent exposure to ore dust. Striking a balance between maintaining productivity and safeguarding worker health is essential. Implementing structured return-to-work evaluations becomes crucial for monitoring health outcomes and ensuring safer working conditions. Case: A 38-year-old male with a one-year history of surface tin mining presented with a persistent cough and worsening shortness of breath. Imaging revealed bilateral nodular opacities, findings consistent with pneumoconiosis. Spirometry demonstrated a restrictive ventilatory defect. No significant comorbidities were identified. Methods: The seven-step PERDOKI protocol was used to assess fitness to work (FTW): (1) task analysis, (2) job demand assessment, (3) medical status evaluation, (4) disability evaluation, (5) risk analysis, (6) environmental tolerance evaluation, and (7) final FTW decision.Results: The miner does not meet the required 7.9 METs threshold for physical capacity. Consequently, he has been classified as “temporarily unfit as a miner.” Medical recommendations include ongoing treatment and a gradual return-to-work schedule, along with regular pulmonary assessments.Conclusion: The PERDOKI 7-step protocol serves as a structured, evidence-based approach to assessing whether a tin miner with pneumoconiosis is ready to return to work. Rather than a one-size-fits-all solution, this protocol emphasizes careful health monitoring and tailored job modifications.